Potensi Ekstrak Daun Kelor (Moringa Oleifera) sebagai Hepatoprotektor pada Tikus Putih (Rattus novergicus) yang Diinduksi Parasetamol Dosis toksik - Noer Kumala Indahsari; masfufatun masfufatun; Emilia Devi D.R (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
Moringa Oleifera is a plant that contains chemical compounds that are useful, such as flavonoids. The ability of this flavonoid compound that can capture free radicals cause damage and hepatoprotektan hepar. Purpose of study was to determined levels of Moringa leaf extract which can overcome the effects of liver damage caused by toxic doses of paracetamol through MDA, SGOT and SGPT Method used in this laboratory experimental study is a Randomized Post Test Only Control Group Design with the following stages: 1. Moringa Leaf Extraction with Ethanol 96%; Try 2.Preparasi animals, 3. Treatment of Animals Try the extract of leaves of Moringa 3 dose is: 250mg / 200BB rat (dose of A), 500mg / 200BB mice (dose B), 1000mg / 200BB mice (dose C) for 14 days in combination with paracetamol 2 g / 200BB mice, compared to the negative control group (group given just paracetamol 2 g / 200BB rat) and the positive control group (the group who were given regular feed) for 14 days.Results : turned out to be no difference in the reduction in SGOT levels are statistically significant between the negative control group with high-dose treatment group ie the dose C with =0,016 smaller than 0.05, whereas a decrease in ALT levels were significantly decreased in the treatment group high dose is the dose C with =0,009 smaller than 0.05. While MDA group treated with the negative control group experienced an overall decline for the dose A with =0,05, dose B with =0,0011 and dose C with =0,001. Conclusion of this study showed that the extract of Moringa leaves can be potentially as an antioxidant in all doses at once can be as hepatoprotektor at high doses is 1000mg / 200BB Rattus Novergicus.